THE REAL DIALOGUE AND THE PHILOSOPHICAL DIALOGUE IN THE MUSNAD OF IMAM ALI (PEACE BE UPON HIM) BY THE SCHOLAR HASAN AL-QABBANJI (1411 AH) - Hanon Mohsen, Prof. Dr. Bushra; Shaker Kazem, Doaa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Dialogical argumentation is one of the methods used in pilgrimage issues and is an interactive communication process between the sender and the addressee through persuasive scientific discussions to reach the desired goal for which this dialogue is held, using evidence and evidential evidence that have a significant impact on the recipient, and argumentative dialogue. In his formative system, it only exists between two coexistent people, namely the argumentative and the argumentative, between whom is a message for which they negotiate in order to reach persuasion. The research came in the Musnad of Imam Ali, because the legacy of Imam Ali (peace be upon him) is one of the scientific hidden things. Which needs to be studied and highlighted in terms of its cultural, scientific, value-based and educational resources.